Towards Which Model of Capitalism Are the Countries of Central and Eastern Europe Going to? Comparative Analysis of this Trajectory and Its Post-Transition Issues (European Journal of Marketing and Economics, 2019)
The end of the Socialist System marked the apparent victory of his adversary: the Capitalist System. Meanwhile the "Recipes" for building the Capitalism in the Countries of the East were Standard and fully complied with the "Washington Consensus" led by the IMF and the World Bank, the reality itself nowadays is facing these Countries with two different challenges. On the one hand, their individual developments during the transition process were very different and their situations quite specific, on the other hand, today they should answer the question towards which model of Capitalism are they going to or privileging: The Anglo-Saxon Model? The German-Scandinavian Model? The French State Capitalism Model, or the Japanese Co-Operative Model?
Keywords: Socialist System, Capitalist System, Models of Capitalism, Western Capitalism, Post-Socialist Capitalism.